Priority Areas and Potential Solutions for Successful Integration and Sustainment of Health Systems Science in Undergraduate Medical Education. (January 2017) - Gonzalo, Jed D.; Baxley, Elizabeth; Borkan, Jeffrey; Dekhtyar, Michael; Hawkins, Richard; Lawson, Luan; Starr, Stephanie R.; Skochelak, Susan
Abstract : Educators, policy makers, and health systems leaders are calling for significant reform of undergraduate medical education (UME) and graduate medical education (GME) programs to meet the evolving needs of the health care system. Nationally, several schools have initiated innovative curricula in both classroom and workplace learning experiences to promote education in health systems science (HSS), which includes topics such as value-based care, health system improvement, and population and public health. However, the successful implementation of HSS curricula across schools is challenged by issues of curriculum design, assessment, culture, and accreditation, among others. In this report of a working conference using thematic analysis of workshop recommendations and experiences from 11 U.S. medical schools, the authors describe seven priority areas for the successful integration and sustainment of HSS in educational programs, and associated challenges and potential solutions. In 2015, following regular HSS workgroup phone calls and an Accelerating Change in Medical Education consortium-wide meeting, the authors identified the priority areas: partner with licensing, certifying, and accrediting bodies; develop comprehensive, standardized, and integrated curricula; develop, standardize, and align assessments; improve the UME to GME transition; enhance teachers' knowledge and skills, and incentives for teachers; demonstrate value added to the health system; and address the hidden curriculum. These priority areas and their potential solutions can be used by individual schools and HSS education collaboratives to further outline and delineate the steps needed to create, deliver, study, and sustain effective HSS curricula with an eye toward integration with the basic and clinical sciences curricula.